KEDUDUKAN CORPORATE GUARANTOR SEBAGAI PIHAK PENJAMIN DEBITUR UTAMA DALAM PROSES KEPAILITAN - DIAH HANDAYANI (PREMISE LAW JURNAL, 2017)
In a guarantee, a guarantor has an extraordinary right required by creditor for released to provide the creditor with safety. The method applied in this research is normative law study method- The position of corporate guarantor that voluntarily release his extraordinary right is same to the main debtor so the corporate guarantor can submit the liquidation with the main debtor. The protection to the corporate guarantee in which the main Debtor did not able to do its liability, the application of liquidation is submitted after all of the property of liquidated debtor is used to pay all of its liability. The protection to the creditor as the holder of corporate guarantor if the main debtor is bankrupt can ask the responsibility of corporate guarantor and if the corporate guarantor is bankrupt, the creditor as the holder of corporate guarantee is take position as concurrent creditor to die corporate guarantor.Keywords : Corporate Guarantor, Main Debtor, Bankruptcy